2016
DOI: 10.1155/2016/5465272
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Study on the Correlation between Tear Film Volume and Tear Film Stability in Diabetic Patients

Abstract: Purpose. To assess the tear film quantity and correlate it with the quality and stability of the tear film in diabetics and compare them to age matched controls. Introduction. Diabetes affects tear film parameters in multiple ways. Poor metabolic control and neuropathy are postulated factors. To further understand how diabetes affects tear film parameters this study was conducted. Subjects and Methods. Tear meniscus height was measured by anterior segment OCT, along with tear thinning time, a subtype of noninv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Blinking plays an important role in maintaining the stability of tear film and is related to psychological and/or several systemic diseases [4, 20, 42]. In this study, we observed the increased blinking frequencies in all diabetes groups, but only the subgroup with diabetic duration of 10 to 20 y reached statistical significance as compared to the healthy controls (Figure 2(i)).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Blinking plays an important role in maintaining the stability of tear film and is related to psychological and/or several systemic diseases [4, 20, 42]. In this study, we observed the increased blinking frequencies in all diabetes groups, but only the subgroup with diabetic duration of 10 to 20 y reached statistical significance as compared to the healthy controls (Figure 2(i)).…”
Section: Discussionsupporting
confidence: 54%
“…For instance, keratoepitheliopathy was evident [37]; corneal sensitivity [711], quantity, and quality of tear secretion [3, 7, 1114] were reduced in diabetic patients; moreover, the alterations in tear composition [15–18] were also detected in the diabetics. However, the factors contributing to the LFU dysfunction are not clear, and they might include the patient's general condition such as age and gender [5, 1921], metabolic control [3, 12, 22, 23], duration of diabetes [20, 21], and occurrence of diabetic microvascular complications [5, 8, 22, 23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lacrimal production is regulated by androgens; thus, age‐regulated production of androgens and estrogen in women impacts ocular surface homeostasis and the PTF stability. Diseases, in general, may also influence the PTF stability, for example, diabetes …”
Section: Resultsmentioning
confidence: 99%
“…DM affects basal tear production more than total tear production and is reflected in our results where Schirmer’s II is significantly reduced in the GDM group. [ 20 ] The reduced values of Schirmer’s I and TBUT in the GDM group although not statistically significant can be explained by involvement of the LFU by DM. [ 8 ] Hyperglycemia via the neural mechanism results in either reduced tear production or an increase in tear evaporation; blink-related abnormalities and alterations in tear film composition also result in DES.…”
Section: Discussionmentioning
confidence: 99%